2013
DOI: 10.1103/physreva.87.013813
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the modulation instability spectrum in optical fibers with oscillating dispersion

Abstract: A simple analytical model is developed to analyze and explain the complex dynamics of the multi-peak modulation instability spectrum observed in dispersion oscillating optical fibers [M. Droques et al., 37, 4832-4834 Opt. Lett., (2012)]. We provide a simple expression for the local parametric gain which shows that each of the multiple spectral components grows thanks to a quasi-phase-matching mechanism due to the periodicity of the waveguide parameters, in good agreement with numerical simulations and experime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 27 publications
7
60
0
Order By: Relevance
“…The first feature is explained by the evolution of the gain coefficient according to Eq. (5) which leads, for some values of the argument, to the annihilation of the sideband amplitude, as it was already confirmed experimentally in [11]. On the other hand, the second feature is linked to FWM between the pump wave and the first QPM sideband, and the subsequent cascading of the FWM process, as it was previously discussed and demonstrated experimentally in [9].…”
Section: Influence Of the Amplitude Of The Dispersion Fluctuationsupporting
confidence: 51%
See 2 more Smart Citations
“…The first feature is explained by the evolution of the gain coefficient according to Eq. (5) which leads, for some values of the argument, to the annihilation of the sideband amplitude, as it was already confirmed experimentally in [11]. On the other hand, the second feature is linked to FWM between the pump wave and the first QPM sideband, and the subsequent cascading of the FWM process, as it was previously discussed and demonstrated experimentally in [9].…”
Section: Influence Of the Amplitude Of The Dispersion Fluctuationsupporting
confidence: 51%
“…. .. More recently, it has been shown that the gain experienced by the pth sidebands after a propagation length L can be predicted by the formula [11]:…”
Section: Model and Situation Under Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…processes such as second harmonic generation and different frequency generation, and QPM can also be used to satisfy the phase-matching conditions for DW generation [27][28][29][30][31].…”
Section: Figmentioning
confidence: 99%
“…The periodic modulation of the waveguide can enable numerous QPM orders, both positive and negative, which can allow QPM-DW generation to the fundamental mode and to higher-order modes (circles), producing a spectrum with many peaks (e). Note: the index curvature is exaggerated to better show phase-matching.arXiv:1710.03821v2 [physics.optics] 7 Dec 2017 2 processes such as second harmonic generation and different frequency generation, and QPM can also be used to satisfy the phase-matching conditions for DW generation [27][28][29][30][31].Here we show that periodic modulations of the effective mode area can enable QPM of DW generation in photonic silicon nitride (Si 3 N 4 ) waveguides, enhancing the intensity of the supercontinuum in specific spectral regions determined by the modulation period. Experimentally, we utilize a sinusoidal modulation of the waveguide width to enable first-order QPM to the TE 20 mode.…”
mentioning
confidence: 99%